2007
DOI: 10.1086/521306
|View full text |Cite
|
Sign up to set email alerts
|

Impact of NS5A Sequences of Hepatitis C Virus Genotype 1a on Early Viral Kinetics during Treatment with Peginterferon‐α2a plus Ribavirin

Abstract: Genetic variability of HCV-1a NS5A does not predict responsiveness to IFN- alpha . Differences in early kinetics during combination therapy are not due to selection of IFN-resistant HCV strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…However, it was observed that the change from isoleucin to valine at position 2252, as compared to the consensus sequence, was positively correlated with a sustained viral response. Similarly, the variability in the V3 region was associated with a sustained viral response, as already reported by others [Murphy et al, 2002;Dal Pero et al, 2007;Jardim et al, 2008]. A significantly higher number of mutations was Fig.…”
Section: Discussionsupporting
confidence: 78%
“…However, it was observed that the change from isoleucin to valine at position 2252, as compared to the consensus sequence, was positively correlated with a sustained viral response. Similarly, the variability in the V3 region was associated with a sustained viral response, as already reported by others [Murphy et al, 2002;Dal Pero et al, 2007;Jardim et al, 2008]. A significantly higher number of mutations was Fig.…”
Section: Discussionsupporting
confidence: 78%
“…To date, the most likely causes for therapeutic failure are non-compliance, insufficient drug levels or dose reductions, drug toxicity, and interruptions in therapy–not resistant, escape variants [85], [86]. In fact, a study of the sequence variability in the NS5A gene during treatment found no selection of interferon resistant HCV strains [87]. Another study of the full length polyprotein also found no significant difference in the number of mutations between non-responders and relapsers [88].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the higher level of serum adiponectin in patients with genotype 2a was demonstrated when compared with that in patients with genotype 1b. It is well known that clinical features and treatment response of CHC are partly determined by several viral factors, including genotype [40][41][42][43]. Among them are viral genotype 1 and high viral load correlated with more necroinflammatory activity, rapid progression of liver disease, and a poor response to antiviral therapy [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that clinical features and treatment response of CHC are partly determined by several viral factors, including genotype [40][41][42][43]. Among them are viral genotype 1 and high viral load correlated with more necroinflammatory activity, rapid progression of liver disease, and a poor response to antiviral therapy [40,41]. Genotype 2, in contrast, might be directly involved in the development of hepatic steatosis in patients with chronic HCV infection [39].…”
Section: Discussionmentioning
confidence: 99%